2022
DOI: 10.1093/femsec/fiac003
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of sulfate-reducing bacteria with formate

Abstract: Despite hostile environmental conditions, microbial communities have been found in µL-sized water droplets enclosed in heavy oil of the Pitch Lake, Trinidad. Some droplets showed high sulfate concentrations and surprisingly low relative abundances of sulfate-reducing bacteria in a previous study. Hence, we investigated here whether sulfate reduction might be inhibited naturally. Ion chromatography revealed very high formate concentrations around 2.37 mM in 21 out of 43 examined droplets. Since these concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In most reservoirs, however, oil is the continuous fluid phase filling the pore volume with discontinuous water filling only a smaller portion of the interstitial pores (Head et al 2003 ). Moreover, Voskuhl et al ( 2021 , 2022 ) revealed strong variability in community composition as well as in ion composition in the water droplets, which by itself provides further evidence for considerable limitation of dispersal as well as diffusion. Together, this indicates that dispersal has had little influence on microbial community composition in the water droplets.…”
Section: Discussionmentioning
confidence: 95%
“…In most reservoirs, however, oil is the continuous fluid phase filling the pore volume with discontinuous water filling only a smaller portion of the interstitial pores (Head et al 2003 ). Moreover, Voskuhl et al ( 2021 , 2022 ) revealed strong variability in community composition as well as in ion composition in the water droplets, which by itself provides further evidence for considerable limitation of dispersal as well as diffusion. Together, this indicates that dispersal has had little influence on microbial community composition in the water droplets.…”
Section: Discussionmentioning
confidence: 95%
“…Following the incubation of oil, heavy oil, or water from oil reservoirs, fermenters frequently emerge as the most prevalent microorganisms (Mbadinga et al, 2011;Zhou et al, 2019b;Pannekens et al, 2021). In most studies on oil reservoir microbiology, sulfate reduction was observed to take a subordinate role due to rapid depletion of sulfate (Jones et al, 2008) or potential inhibition of the sulfate-reducing bacteria (Voskuhl et al, 2022). Typically when sulfate concentrations exceed 50 μM, sulfate reduction becomes the prevailing degradation process (Jimenez et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…While formate in high concentrations can be toxic to some living organisms, , it represents a harmless and highly soluble C 1 compound to readily provide reducing power to artificial cells designed in a bottom-up fashion. Since it does not require a membrane transporter to cross phospholipid bilayers in the millisecond time scale, formate provides the advantage of requiring exclusively a NAD­(P) + -dependent formate dehydrogenase (FDH) to reduce the nicotinamide cofactor, while CO 2 is formed as a reaction product.…”
Section: Formatementioning
confidence: 99%